A new perspective from English language teaching. Invisible learning and its contributions to foreign language acquisition (Revista Innova Educación, 2021)
“The invisible is not what does not exist, but what we cannot observe." The objective of this research is to determine the impact of the invisible learning of Moravec and Cobo (2011) on the acquisition of the English language. To this end, the available scientific literature was reviewed, proceeding later to argue the benefits of invisible learning in learning English with technological tools. The emergence of new technologies requires that teachers act in an innovative way by applying teaching strategies that facilitate the educational achievement of the student, developing social, reflective and cognitive skills. Said learning is no longer only conceived as the incorporation of new grammatical structures, but with the learning of a new culture. From the trial, it was possible to conclude that invisible learning shows a relevant role when learning a foreign language due to its characteristics that incorporate ICTs and gamification, which are highly accepted and motivating for students in the classroom.
Keywords: English learning; virtual learning; soft skills; technological tools; innovation